Integrating computational thinking into mathematics education through an unplugged computer science activity - Filiz Mumcu; Esra Kıdıman; Fatih Özdinç (Journal of Pedagogical Research, 2023)
Integrating computational thinking (CT) into various disciplines via computer science (CS) methods such as unplugged, block-based, text-based, and physical programming is a trending topic in educational sciences. This study presents a perspective on implementing an unplugged computer science activity to integrate CT into mathematics education. This study aims to examine the integration of CT into mathematics education, its classroom practice, and the opinions of students and pre-service teachers towards the unplugged CS activity. For this purpose, we developed an unplugged CS activity, which includes CT components, computer science and mathematics education achievements. The unplugged CS activity is a problem of transmitting data most efficiently and accurately between transmitter and receiver. The researchers trained twelve pre-service mathematics teachers to implement this activity in real-classroom environments. The pre-service teachers implemented the unplugged CS activity with 80 students in four classes. CT components were considered in the activity design. The students performed data collection, data analysis, decomposition, pattern recognition, algorithm design, and testing and debugging, which are components of CT, during the activity. Middle school students stated that they had enjoyed the activity and that this activity made the mathematics learning process satisfying. They established a relationship between the activity and mathematics education, besides, they needed help connecting it with CS concepts. Pre-service teachers stated that they had challenges in classroom management during the activity. Classroom management should be a part of teacher education in designing and implementing CT-integrated lessons. Courses containing classroom management, CS activity design and implementation should be developed for pre-service teachers based on theory and practice within their discipline.